2006
DOI: 10.1186/1471-2164-7-207
|View full text |Cite
|
Sign up to set email alerts
|

A general pipeline for the development of anchor markers for comparative genomics in plants

Abstract: Background: Complete or near-complete genomic sequence information is presently only available for a few plant species representing a large phylogenetic diversity among plants. In order to effectively transfer this information to species lacking sequence information, comparative genomic tools need to be developed. Molecular markers permitting cross-species mapping along co-linear genomic regions are central to comparative genomics. These "anchor" markers, defining unique loci in genetic linkage maps of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 38 publications
(38 reference statements)
0
28
0
Order By: Relevance
“…The number of bands in these species ranged from 1 to 3, of sizes between 150 to 900 bps (Figure  3). When these primer pairs were tested with rice, maize and sorghum, the cross-transferability was 73.7%, 78.9% and 68.4% respectively [30]. This high level of cross-species reactivity was expected, as these markers were designed by merging sugarcane ESTs with homologous ESTs of sorghum a barley, along with genomic sequences of rice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of bands in these species ranged from 1 to 3, of sizes between 150 to 900 bps (Figure  3). When these primer pairs were tested with rice, maize and sorghum, the cross-transferability was 73.7%, 78.9% and 68.4% respectively [30]. This high level of cross-species reactivity was expected, as these markers were designed by merging sugarcane ESTs with homologous ESTs of sorghum a barley, along with genomic sequences of rice.…”
Section: Resultsmentioning
confidence: 99%
“…[26] designed and developed 76 CISP markers, of which, 56 (73.7%) and 43 (56.6%) markers were tested for cross-species amplification in bean and peanut, respectively. It has also been reported that CISPs are an effective means to explore poorly characterised genomes, for both, DNA polymorphism and non-coding sequence conservation on a genome-wide or candidate-gene basis, and to provide anchor points for comparative genomics, across a diverse range of species [30]. Recently, Zeid et al .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of species with unsequenced genomes such an approach is still desirable in comparative studies. The gene-based STS legume anchor markers (Leg markers) used in this study were designed to facilitate the comparative genomics of less known legumes (Fredslund et al, 2006;Hougaard et al, 2008). To date these markers have been successfully applied in the synteny analyses of Phaseolus vulgaris, Lotus japonicas, Medicago truncatula and Arachis (Hougaard et al, 2008;Bertioli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…With the availability of whole-genome sequences of crops and plant species, as well as other genomic resources (e.g. microarray methods, expressed sequence tag (EST) libraries, high throughput resequencing technologies), have extended the comparative method to encompass the evolution of genome structure and function [25,26].…”
Section: Genomics Assisted Crop Breeding and Improvementmentioning
confidence: 99%